IMPLEMENTASI TEKNOLOGI PEMBELAJARAN DI MADRASAH IBTIDAIYAH MUHAMMADIYAH KARANGWARU PLUPUH - Isnaini Isnaini; Siti Halimah; Budi Murtiyasa; Masduki Masduki (STKIP Pesisir Selatan, 2026)
This study aims to describe the implementation of learning technology at Madrasah Ibtidaiyah Muhammadiyah Karangwaru Plupuh Sragen, identify enabling and constraining factors, and interpret its impact on student engagement. A qualitative case study with a descriptive approach was employed. Data were collected through in-depth interviews with three key informants—Umi Khasanah (principal), Zuli Nurdayati (class teacher), and Sitisamlatun (class teacher)—supported by classroom observations and document review (lesson plans, digital media artifacts, and assessment evidence). Data analysis followed thematic coding, data reduction and display, and conclusion drawing with source and technique triangulation to enhance trustworthiness. The main findings indicate that technology was integrated in three domains: planning (using digital resources to design learning materials), implementation (audiovisual media, interactive quizzes, and learning communication through messaging applications), and assessment (simple platform-based formative tests and digital portfolio documentation). Most practices remain at substitution–augmentation levels, yet initial movement toward modification is evident when teachers redesign learning flows into collaborative and project-based micro-tasks. Enablers include the principal’s instructional leadership, peer-sharing culture, and parent partnership; major barriers involve limited devices, unstable internet connectivity, and varied teacher digital literacy.